Validation of self-report and hospital pill count using unannounced home pill count as methods for determination of adherence of antiretroviral therapy. - Minzi, OM; Naazneen, AS (Tanzania Journal of Health Research, 2008)
Adherence to anti-retroviral therapy (ART) is very crucial for successful treatment outcomes. This study aimed to validate patient-self report (PSR) and hospital based pill count (HoPC) as adherence determination methods by using unannounced home visit pill count (HPC). The study was carried out at Muhimbili National Hospital in Dar es Salaam,Tanzania and 215 patients purposively selected were recruited. On refi ll day, the remaining pills were counted. They were also asked to report on the number of doses they missed during the past 28 days. They were later visited in their homes without appointment where the remaining pills were counted. Ninety-eight percent and 93% reported to adhere to ART by PSR method and HoPC, respectively. However, only 58% of the same study patients were found to be adherent by ≥ 95% using HPC. In conclusion, PSR and HoPC do not always give reliable adherence data in patients undergoing ART. Therefore, we recommend application of combination methods for adherence measuring in patients starting to include patient self report and hospital based pill count in new patients and complementing them with unannounced home based pill count in experienced patients. Wherever possible, drug plasma concentration measurements should also be established. Keywords: anti-retroviral therapy, adherence, self-report, pill count, HIV/AIDS, Tanzania Tanzania Journal of Health Research Vol. 10 (2) 2008: pp. 84-88